The effect of physical exercise on disordered social communication in individuals with autism Spectrum disorder: a systematic review and meta-analysis of randomized controlled trials - Jia, Shuqi; Guo, Chengcheng; Li, Shufan; Zhou, Xiaojing; Wang, Xing; Wang, Qiang (Frontiers in Pediatrics, 2023)
Objective: The aim of this systematic review and meta-analysis was to systematically investigate the intervention effect of physical exercise on disordered social communication in patients with autism spectrum disorders. Methods: This systematic review and meta-analysis used the PubMed, Web of Science, the Cochrane Library, and Embase electronic databases to conduct a systematic search of literature describing randomized controlled trials (RCTs) on the effect of physical exercise on disordered social communication in autistic patients from the first year of inclusion to 21 January 2023. Results: A total of 14 RCTs including 460 autistic patients were analyzed. A meta-analysis showed that physical exercise had a positive effect on social communication disorder (SMD = 0.45, 95% CI: 0.15, 0.74, p < 0.05) in autistic patients. Subgroup analysis showed that exercise programs with multiple components (SMD = 0.73, 95% CI: 0.39, 1.06, P < 0.001), a moderate duration (SMD = 0.73, 95% CI: 0.38, 1.08, P < 0.001), a moderate-high frequency (SMD = 0.84, 95% CI: 0.53, 1.14, P < 0.001), and a long duration (SMD = 0.77, 95% CI: 0.36, 1.18, P < 0.001) led to significant improvement. Conclusion: Physical exercise can improve disordered social communication in patients with autism spectrum disorders. Specifically, early intervention, multi-component exercise, a moderate period, moderate and high frequency, long duration, and multi-participant programs were most effective.